Individual vs. Group Cognitive Behavior Therapy for Anxiety Disorder in Children and Adolescents: A Meta-Analysis of Randomized Controlled Trials - Guo, Tingting; Su, Jing; Hu, Jiayi; Aalberg, Marianne; Zhu, Yinglin; Teng, Teng; Zhou, Xinyu (Frontiers in Psychiatry, 2021)
Background: Anxiety disorder is the most prevalent mental disorder in children and adolescents. However, evidence for efficacy and acceptability between individual cognitive behavior therapy (I-CBT) and group cognitive behavior therapy (G-CBT) in anxiety disorders in children and adolescents remains unclear. Methods: Eight electronic databases (PubMed, Embase, Cochrane, Web of Science, CINAHL, PsycINFO, ProQuest and LILACS) were searched from inception to October 2019. Randomized controlled trials comparing I-CBT with G-CBT for anxiety disorders in children and adolescents were included. Primary outcomes were efficacy (mean change in anxiety symptom scores) at post-treatment and acceptability (all-cause discontinuation). Secondary outcomes were remission at post-treatment. Subgroup analyses were also conducted to examine whether result would be influenced by the age, the number of treatment sessions, parental involvement, male/female, and number of participants. Result: Nine studies were selected in this meta-analysis. The pooled analyses indicated no significant difference between I-CBT and G-CBT for efficacy at post-treatment (standardized mean difference [SMD], -0.14; 95% confidence interval (CI), -0.37 to 0.09), acceptability (odds ratio [OR], 1.30; 95% CI, 0.61 to 2.77) and remission at post-treatment (OR, 1.15; 95% CI, 0.79 to 1.66). In the subgroup analysis of age, I-CBT was significantly more effective than G-CBT in adolescents at post-treatment (SMD, -0.77; 95% CI, -1.51 to -0.02), but not in children (SMD, 0.00; 95% CI, -0.02 to 0.20). However, the findings were not materially different from those of the efficacy subgroup analysis of number of treatment sessions, parental involvement, male/female, and number of participants. Conclusions: Based on those current evidences, I-CBT showed more beneficial than G-CBT for anxiety disorders in adolescents, but not in children. However, further well-designed clinical studies should be performed to confirm these findings.